PENGEMBANGAN ALAT LEMBING PORTABLE - Ridha Sabda Utami; Andika Triansyah; Mimi Haetami (Universitas Tanjungpura, 2019)
Abstract This study aims to develop a media or a portable javelin tool that can be assembled so that it is practical in the process of training for the javelin throwers and in the learning process at schools and also to determine the feasibility of portable javelin tool based on the validity aspects and its practicality. This portable javelin is made by using mixture of basic materials from several composites namely fiberglass fiber, polyester resin and catalyst. This study is a developmental research. This study uses the ADDIE developmental model (Analysis, Design, Development, Implementation and Evaluation). Data collection techniques in this study used field trials and questionnaire methods. The result of this research and development is a portable javelin tool. The result of the analysis of the feasibility level of the portable javelin tool are : (1) The validity test of 2 validators, namely media experts shows a score of 85,42 % and practitioner shows a score of 87,5 %. Therefore the portable javelin tool is include in the category of “Very Valid”. (2) The test of acceptability and practicality through the user responses, namely sport students, shows an average score of 91,16 %. Therefore from that it can be concluded that the portable javelin tool is feasible to use and practical in its use. Keywords : Development, Javelin, Portable